2014
DOI: 10.1002/ajhb.22598
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of pica and micronutrient status

Abstract: Objectives Pica is the craving for and consumption of non-food items, including the ingestion of earth (geophagy), raw starch (amylophagy), and ice (pagophagy). Pica has long been associated with micronutrient deficiencies, but the strength of this relationship is unclear. We aimed to evaluate the association between pica behavior and the risk of being anemic or having low hemoglobin (Hb), hematocrit (Hct), or plasma zinc (Zn) concentrations. Methods We systematically reviewed studies in which micronutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 65 publications
4
68
1
1
Order By: Relevance
“…In the observed population pica was not regarded as stigmatized culture, rather a divergent behaviour (20). In studies from the United States of America the prevalence of pica in children ranged between 10.0% and 18.5% (7,10). The differences may be explained by the distinct definitions of pica and the parents' unwillingness to declare their child's behaviour abnormal.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the observed population pica was not regarded as stigmatized culture, rather a divergent behaviour (20). In studies from the United States of America the prevalence of pica in children ranged between 10.0% and 18.5% (7,10). The differences may be explained by the distinct definitions of pica and the parents' unwillingness to declare their child's behaviour abnormal.…”
Section: Discussionmentioning
confidence: 96%
“…These findings differ from those of some other studies (3,19,23,24). But at least 2 double blind controlled studies did not find any relationship between iron therapy and pica behaviour (10). This is probably because pica is more a cultural behaviour than a result of iron deficiency.…”
Section: ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشون‬ ‫و‬ ‫الثالث‬ ‫اmentioning
confidence: 91%
See 1 more Smart Citation
“…45,46 A recent meta-analysis found that pica was significantly associated with an increased risk for anemia and low hemoglobin, hematocrit, and plasma zinc. 27 However, there are no published studies that we are aware of that have been able to establish a causal relationship between geophagy and micronutrient status. Two randomized controlled trials conducted to determine the impact of iron supplementation on geophagy in children found no significant reduction in geophagy behavior among study children with supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Furthermore, these findings suggest that geophagy may be a potential risk factor for EE and stunting in pediatric populations. However, there are very few published studies assessing geophagy in pediatric populations, [23][24][25][26][27] and none assessing the role of this behavior in EE or stunting.…”
Section: Introductionmentioning
confidence: 99%